AGRESIVITAS PELAPORAN KEUANGAN, AGRESIVITAS PAJAK, TATA KELOLA PERUSAHAAN DAN KEPEMILIKAN KELUARGA - Hanna, Hanna; Haryanto, Melinda (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2016)
Tax revenue in Indonesia until 2014 contributed approximately 78% of total state revenue. This shows that the tax is important both for the country as a source of income, as well as for the company as a taxpayer. For companies, the tax to be paid is a burden for the company which will reduce net income. Based on earlier research, the management company will tend to act aggressive tax in financial reporting. Tax aggressiveness influenced also by the pattern of ownership of the company in which the role of corporate governance are expected to influence the direction of the management decision-making. The purpose of this study was to examine the effect of financial reporting aggressiveness, family ownership and corporate governance against tax aggressiveness. The samples are all companies listed on the Indonesian Stock Exchange (BEI) except finance, insurance and banks during the period 2010-2014. The method used is multiple regression method. The results showed that the audit committee and institutional ownership has a significant influence on the aggressiveness of the taxes while the aggressiveness of financial reporting and the ownership of the family did not have a significant effect on the aggressiveness of the tax.